2012
DOI: 10.3122/jabfm.2012.06.110325
|View full text |Cite
|
Sign up to set email alerts
|

Health Perceptions and Levels of Attachment: Owners and Pets Exercising Together

Abstract: Background: Obesity is a parallel problem in canine and human populations. We describe health perceptions and levels of companion animal attachment in a cohort of dog owners.Methods: As part of a larger trial examining the impact of veterinary counseling on activity levels of dog owners and their pets, owners presenting to a veterinary referral center were asked to self-report perceived levels of health and attachment to their dog (Lexington Attachment to Pets Scale). Owner body mass index and the body conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 9 publications
(7 reference statements)
1
27
0
Order By: Relevance
“…The mechanism behind this association is unknown, but it has been speculated that pet dogs may serve as a surrogate support network for their owners, particularly when owners have less perceived peer social support. (Stephens et al, 2012) Child obesity has been associated with numerous mental health concerns as well as a social stigma, which is consistent with the findings in this and other studies where overweight/obese children report less perceived social support from peers. However, because dog attachment was also measured in the same population, this study highlights a potential mechanism that explains a higher dog attachment in overweight/obese children, in which dogs could be taking the place of peer social support due to the unconditional love from dogs that children report.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The mechanism behind this association is unknown, but it has been speculated that pet dogs may serve as a surrogate support network for their owners, particularly when owners have less perceived peer social support. (Stephens et al, 2012) Child obesity has been associated with numerous mental health concerns as well as a social stigma, which is consistent with the findings in this and other studies where overweight/obese children report less perceived social support from peers. However, because dog attachment was also measured in the same population, this study highlights a potential mechanism that explains a higher dog attachment in overweight/obese children, in which dogs could be taking the place of peer social support due to the unconditional love from dogs that children report.…”
Section: Discussionsupporting
confidence: 92%
“…One study found that increasing body mass index (BMI) is associated with greater pet attachment and less perceived social support. (Stephens et al, 2012) However, this has not been studied in overweight children. More in-depth knowledge is needed to understand this relationship in children, especially children who are overweight/obese.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a nationwide sample of older adults, strong pet attachment was associated with less depression among those who recently experienced a death in the family (Garrity et al, 1989). Furthermore, in a sample of dog owners, pet attachment was associated with owner weight status and owner perceptions of human social support (Stephens et al, 2012).…”
Section: Theoretical Frameworkmentioning
confidence: 98%
“…The initial triglyceride level was 152.14 mg/dL (SD = 168.22) in the PA group (n = 22) and 161.88 mg/dL (SD = 1224.71) in the SC group (n = 8); the post-intervention triglyceride level was 180 mg/dL (SD = 260.79) in the PA group and 115.13 mg/dL (SD = 87.87) in the SC group. Other outcome measures have been reported elsewhere (Stephens et al 2012;Netting et al in press).…”
Section: Dog Owner Outcome Measuresmentioning
confidence: 99%